Evaluation of the phytoremediation potential of two medicinal plants - Fazilah Abd Manan,; Tsun, Thai Chai; Azman Abd Samad,; Dayangku Dalilah Mamat, (Universiti Kebangsaan Malaysia, 2015)
Heavy metal pollution leads to human health problems and represents a constant threat to the environment. Pollutant clean-up using conventional methods are often hampered by high cost and ineffective pollutant removal. Phytoremediation technique is a preferable alternative due to its minimal side effects to the environment in addition to reasonable treatment cost. In this study, we investigated the potential of Centella asiatica and Orthosiphon stamineus as phytoremediation agents. Both species were grown in contaminated soil obtained from industrial land. Plant growth response and their ability to accumulate and translocate zinc, copper and lead were assessed. From this study, root growth of C. asiatica was compromised when grown in contaminated soil. Copper was highly accumulated in C. asiatica roots while the leaves were more concentrated with zinc and lead. Conversely, all three tested metals were highly detected in the roots of O. stamineus, although the root elongation was not adversely affected. Low amount of metals in the stems of both species permits longer stem length. Correlation study showed that the accumulation of zinc, copper and lead in plant tissues varies depending on plant species and the type of metals. Based on the bioaccumulation, translocation and enrichment factor, our study showed that C. asiatica was tolerant towards zinc, copper and lead; hence suitable for phytoextraction. By contrast, O. stamineus acted as a moderate accumulator of the tested metal elements.